ANALISIS KEBIJAKAN PROGRAM RESTRUKTURISASI POLIS PT ASURANSI JIWASRAYA (PERSERO) DITINJAU DARI ASPEK PERJANJIAN (STUDI KASUS: PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR 09/PDT.G.S/2021/PN.JKT.PST) - Yeremia Wijaya; Vera W. S. Soemarwi (Jurnal Hukum Adigama, 2022)
Since 2018, PT Asuransi Jiwasraya (Persero) has delayed payment of claims due to financialdif iculties. The financial condition that kept getting worse brought the oldest insurance companyin Indonesia to default. In order to overcome the default, Jiwasraya conducted a PolicyRestructuring Program. This Policy Restructuring Program basically reduces the insureds’ policyvalue. The problems raised in this research are how the legal review of the Policy RestructuringProgram of PT Asuransi Jiwasraya (Persero) based on the agreement and how the legal protectionfor the insured and/or policyholders who feel aggrieved due to the Policy Restructuring Programof PT Asuransi Jiwasraya (Persero). Meanwhile, this research is a type of normative legalresearch that is descriptive analytical based on secondary data collected and analyzed throughlibrary research. The results of this study indicate that the Policy Restructuring Program is a debtor liability restructuring which in its implementation violates the principles of agreement in theCivil Code, Commercial Code, and General Policy Conditions. Legal protection for customerswho feel aggrieved due to the Policy Restructuring Program is regulated in the ConsumerProtection Act and POJK 1/2013. Suggestions for the Financial Services Authority to makeregulations that strictly stipulate that debt or liability restructuring in insurance companies mustbe based on the agreement of both parties in accordance with the principle of agreement, while forPT Asuransi Jiwasraya (Persero) to eliminate discriminatory treatment against customers whoparticipate and do not participate the Policy Restructuring Program.